FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH PRODUKSI USAHA TAMBAK IKAN DI GAMPONG BATUPHAT BARAT KECAMATAN MUARA SATU KOTA LHOKSEUMAWE - Aries Munandar; Cut Putri Mellita Sari (LPPM UNIMAL, 2019)
The purpose of this study is to determine the effect of capital, land area and labor on the production of fish ponds in the village of Batuphat Barat, Muara Satu Subdistrict, Lhokseumawe City. This study uses primary data. Methods of data analysis using Multiple Linear Regression. Partially stated that the Capital variable had a positive and significant effect on the amount of fish farm production in the village of Batuphat Barat, Muara Satu Subdistrict, Lhokseumawe City, while the Land Area and Labor had no significant, but positive effect the number of fish farm production in the village of Batuphat Barat, Muara Satu Subdistrict, Lhokseumawe City. Simultaneously stating that the Capital variable, Land Area and Labor together (simultaneously) has a significant effect on the amount of fish pond business production in the village of Batuphat Barat, Muara Satu Subdistrict, Lhokseumawe City.